DAYA SAING EKONOMI PROVINSI JAMBI - Sudirman, Sudirman; Susilawati, Susilawati (Fakultas Ekonomi Universitas IBA, 2019)
In this study, we want to see the economic basis and pattern of economic structure in JambiProvince, This study uses secondary data, namely Jambi Provisional PDRB and 11 municipaldistricts in Jambi province in 2010 - 2017 in this study to see the basis of the economy and the mixof economic sectors in Jambi province using the LQ model and the classification typology. Theresults of this study indicate that from the results of the classic typology analysis, it can be seen thatthe patterns and structure of economic growth from 9 districts and 2 cities in Jambi Province, WestTanjung Jabung and East Tanjung Jabung districts are classified into Quadrant III decliningprosperous regions (potential to be left behind ), which means that the rate of growth and incomeper capita of Tanjung Jabung Barat district is higher than the per capita income of Jambi Provinceand the growth rate of Tanjung Jabung Barat district is lower than the rate of growth of JambiProvince. Whereas the City of Full Sei is classified into the prospereus quadrant type I area whichmeans that the per capita income of Sei Full City is greater than the income of the Perkapita ofJambi Province and the growth rate of the city of Full Sei is greater than the Growth Rate in JambiProvince.